2017
DOI: 10.3390/rs10010050
|View full text |Cite
|
Sign up to set email alerts
|

Improving Selection of Spectral Variables for Vegetation Classification of East Dongting Lake, China, Using a Gaofen-1 Image

Abstract: Abstract:There is a large amount of remote sensing data available for land use and land cover (LULC) classification and thus optimizing selection of remote sensing variables is a great challenge. Although many methods such as Jeffreys-Matusita (JM) distance and random forests (RF) have been developed for this purpose, the existing methods ignore correlation and information duplication among remote sensing variables. In this study, a novel approach was proposed to improve the measures of potential class separab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
(64 reference statements)
0
11
0
Order By: Relevance
“…The DC-FSCK can examine the linear and nonlinear relationships between feature variables and GSV and consider the self-correlation and combination effects among the feature variables. The SRA and RF can only select the variables with good linear correlation or importance, but discard the rest variables that might have a high saturation level and contain useful information [19]. Song et al [19] proposed a spectral variable selection method by integrating Jeffreys-Matusita distance and correlation among feature variables for image classification of wetlands and found that their method offered greater potential than RF.…”
Section: Effective Methods For Improving Spectral Variable Selection mentioning
confidence: 99%
See 4 more Smart Citations
“…The DC-FSCK can examine the linear and nonlinear relationships between feature variables and GSV and consider the self-correlation and combination effects among the feature variables. The SRA and RF can only select the variables with good linear correlation or importance, but discard the rest variables that might have a high saturation level and contain useful information [19]. Song et al [19] proposed a spectral variable selection method by integrating Jeffreys-Matusita distance and correlation among feature variables for image classification of wetlands and found that their method offered greater potential than RF.…”
Section: Effective Methods For Improving Spectral Variable Selection mentioning
confidence: 99%
“…The SRA and RF can only select the variables with good linear correlation or importance, but discard the rest variables that might have a high saturation level and contain useful information [19]. Song et al [19] proposed a spectral variable selection method by integrating Jeffreys-Matusita distance and correlation among feature variables for image classification of wetlands and found that their method offered greater potential than RF. However, their method ignores the combination effects of the feature variables.…”
Section: Effective Methods For Improving Spectral Variable Selection mentioning
confidence: 99%
See 3 more Smart Citations